KONSUMSI SIRIH PINANG DAN PATOLOGI GIGI PADA MASYARAKAT PRASEJARAH LEWOLEBA DAN LIANG BUA, DI NUSA TENGGARA TIMUR, INDONESIA - Toetik Koesbardiati; Delta Bayu Murti (Balai Arkeologi Yogyakarta, 2019)
This paper focus on chewing betel quid habit that dominantly happen in the Asia to Pacific region. Betel quid leaves traces of reddish-brown colour on the teeth. It was identified that dental stain was very common on teeth of prehistoric skeletal remains, for example in Thailand and Vietnam. Several studies have shown that chewing betel nut can cause diseases in the teeth and oral cavity. The purpose of this study is to describe the relationship between betel nut chewing and the emergence of tooth pathology in teeth from the prehistoric population from Lewoleba and Liang Bua. Ten individuals were observed using the macroscopic method. The results showed that consumption of betel nut (based on dental stains) was followed by attrition, periodontitis and even antemortem tooth loss.